2017
DOI: 10.1016/j.resuscitation.2017.02.014
|View full text |Cite
|
Sign up to set email alerts
|

e-Learning in Advanced Life Support—What factors influence assessment outcome?

Abstract: Clinical experience through membership of cardiac arrest teams and previous ILS or ALS training were independent predictors of performance on the ALS course whilst time spent accessing e-learning materials did not affect course outcomes. This supports the blended approach to e-ALS which allows participants to tailor their e-learning experience to their specific needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
2
13
0
1
Order By: Relevance
“…The study by Thorne et al concluded by affirming the equivalence in the learning of ALS with both didactic methodologies and that courses with mixed methodology with e-learning should be promoted. As a continuation of this work, Thorne et al [ 21 ] found that the time spent accessing e-learning materials did not affect the results of the course. In our setting, Castillo’s studies (2018 and 2020) [ 10 , 13 ] can be highlighted, although both are studies related to basic life support training.…”
Section: Discussionmentioning
confidence: 52%
“…The study by Thorne et al concluded by affirming the equivalence in the learning of ALS with both didactic methodologies and that courses with mixed methodology with e-learning should be promoted. As a continuation of this work, Thorne et al [ 21 ] found that the time spent accessing e-learning materials did not affect the results of the course. In our setting, Castillo’s studies (2018 and 2020) [ 10 , 13 ] can be highlighted, although both are studies related to basic life support training.…”
Section: Discussionmentioning
confidence: 52%
“…E-learning prior to the advanced life support (ALS) course for medical professionals resulted in equal overall scores for practical skills when compared with traditional training in ALS. However, the e-learning reduced the total time of the education and the number of instructors and generated economic benefits [1315]. Technological learning activities in BLS for laymen may also be cost effective [41] and may match the workplace structure for learning [39].…”
Section: Discussionmentioning
confidence: 99%
“…Uma estratégia para manter a retenção das habilidades, conforme proposto em outras publicações, 17,24 seria um retreinamento periódico como, por exemplo, e-learning. Porém, uma questão ainda não respondida seria qual o intervalo e periodicidade do treinamento, qual tipo de treinamento e para qual tipo de população (profissionais da saúde ou não, que atuam em locais com elevada ocorrência de eventos de PCR).…”
Section: Discussionunclassified